The Effect of Student Team Work Learning (STWL) towards Students’ Reading Comprehension - Terasne, Terasne; Permana, Dira; Setianingsih, Tri (LPPM Universitas Bumigora Mataram, 2020)
This research was aimed at finding out whether or not Student Team Work Learning Strategy (STWL) has positive effect on students’ reading comprehension. The research was pre experimental with one pre-test post-test design. The sample of the study was second grade students of MA Nurul Muhsini Jomang Batu Jai Lombok Tengah which consisted of one class 30 students. The instrument used was reading test inthe form of multile chose test and objective test which were consited of 25 items. The score was analyzed by using descriptive and inferential analysis. Descriptive analysis was used to describe mean, mode, median, and standard deviation of group, and inferential analysis was used to describe the value of t-test for comparison between t-table. It was showed that the value of t-test = 5.411 was higher than the value of t-table = 1.692. Alternatively, using Student Team Work Learning Strategy has positive effect on students’ reading comprehension at second grade students of MA Nurul Muhsini Jomang Batu Jai Lombok Tengah.